Associations between a history of sexual abuse and dental anxiety, caries experience and oral hygiene status among adolescents in sub-urban South West Nigeria - Morenike Oluwatoyin Folayan; Maha El Tantawi; Nourhan M. Aly; Abiola Adetokunbo Adeniyi; Elizabeth Oziegbe; Olaniyi Arowolo; Michael Alade; Boladale Mapayi; Nneka Maureen Chukwumah; Olakunle Oginni; Nadia A. Sam-Agudu (BMC Oral Health, 2023)
10p